Maxwell's Equations : Analysis and Numerics - Langer, Ulrich; Pauly, Dirk; Repin, Sergey (De Gruyter, 2019)
This volume collects longer articles on the analysis and numerics of Maxwell's equations. The topics include functional analytic and Hilbert space methods, compact embeddings, solution theories and asymptotics, electromagnetostatics, time-harmonic Maxwell's equations, time-dependent Maxwell's equations, eddy current approximations, scattering and radiation problems, inverse problems, finite element methods, boundary element methods, and isogeometric analysis.- Resumé vydavatel
Keywords: Maxwellovy rovnice; metoda konečných prvků; Maxwell equations; finite element method; elektronické knihy; sborníky; electronic books; papers of several authors